Does the FIFA 11+ prevention programme improve sprint time in adolescent elite male football players?: A randomized controlled trial - Rolstad-Martinez, L. E. (NIH, 2017)
Introduction: Sprinting is an important element of football and its importance to the sport is increasing. The total sprinting distance performed by any player during a football match average to 385+/-223 metres. Analysis of sprinting distances and duration from two UEFA Europa League seasons show that 90 percent of sprints were shorter than 5 seconds, whereas 10 percent were longer than 5 seconds. With the increasing demands to sprinting ability in football the susceptibility to injury also rise. Muscle injuries are the most common injury to the lower extremity in professional football. The purpose of this study was to further investigate the results from the FIFA 11+ study "Including the Copenhagen Adduction Exercise in the FIFA 11+ Provides Missing Eccentric Hip Adduction Strength Effect in Male Soccer Players (Haroy et al., 2017)" in regards to sprint times. Through a randomised controlled trial these results are used to see if the FIFA 11+ can improve sprint performance in young elite football players. The correlation between sprint times and hamstring strength will also be explored in this master thesis. The theory behind the modern game of football and sprinting in football is a basis for this thesis, along with the principles of sprinting in the FIFA 11+ warm-up program, importance of hamstring strength in sprinting, how to improve sprinting in football and sprint related injuries. Objective: The overall aim of this project is to examine whether the FIFA 11+ with the Nordic Hamstring or Copenhagen Adduction exercise affects the sprint times in elite youth football players. Methods: This master thesis will look into the results of the changes in sprint time after an 8-week intervention program utilizing the FIFA 11+ warm-up program, a randomized controlled trial. Main outcome: Within- and between-group differences in sprint time (s) from baseline to post-test. Results: Between-group and within-group analyses showed no significant difference in sprint times at any sprint interval. Conclusions: The results from the present study could not produce any effect from the FIFA 11+ warm-up program on sprint times.